La dette infinie : représentations africaines, solidarité écologique et développement durable - Étienne Le Roy (VertigO)
The practical experience of a legal anthropology applied to African countries and peoples for the beginning of the 1960 years leads to underline the existence of representations of world, law and debt with a twofold lesson. First, local cultures ares rational but according to original premises founded on communautarism linked to what our western societies try out in premodernity ages. Second, the idea of infinite debt, like a chemical or mathematical formula, illustrate complexity of the extent and outcomes of intergenerational obligations in a context of renewal of the commons and sustainable development.